Modulation of induced cytotoxicity of doxorubicin by using apoferritin and liposomal cages - Gumulec, Jaromir; Fojtu, Michaela; Raudenska, Martina; Sztalmachova, Marketa; Skotakova, Anna; Vlachova, Jana; Skalickova, Sylvie; Nejdl, Lukas; Kopel, Pavel; Knopfova, Lucia; Adam, Vojtech; Kizek, Rene; et al. (International journal of molecular sciences, 2014)
Doxorubicin is an effective chemotherapeutic drug, however, its toxicity is a significant limitation in therapy. Encapsulation of doxorubicin inside liposomes or ferritin cages decreases cardiotoxicity while maintaining anticancer potency. We synthesized novel apoferritin- and liposome-encapsulated forms of doxorubicin ("Apodox" and "lip-8-dox") and compared its toxicity with doxorubicin and Myocet on prostate cell lines. Three different prostatic cell lines PNT1A, 22Rv1, and LNCaP were chosen. The toxicity of the modified doxorubicin forms was compared to conventional doxorubicin using the MTT assay, real-time cell impedance-based cell growth method (RTCA), and flow cytometry. The efficiency of doxorubicin entrapment was 56% in apoferritin cages and 42% in the liposome carrier. The accuracy of the RTCA system was verified by flow-cytometric analysis of cell viability. The doxorubicin half maximal inhibition concentrations (IC50) were determined as 170.5, 234.0, and 169.0 nM for PNT1A, 22Rv1, and LNCaP, respectively by RTCA. Lip8-dox is less toxic on the non-tumor cell line PNT1A compared to doxorubicin, while still maintaining the toxicity to tumorous cell lines similar to doxorubicin or epirubicin (IC50 = 2076.7 nM for PNT1A vs. 935.3 and 729.0 nM for 22Rv1 and LNCaP). Apodox IC50 was determined as follows: 603.1, 1344.2, and 931.2 nM for PNT1A, 22Rv1, and LNCaP.
Keywords: doxorubicin; apoferritiny; viabilita buněk; protinádorová antibiotika; Cell Line, Tumor; Liposomes; vztah mezi dávkou a účinkem léčiva; Cell Survival; Inhibitory Concentration 50; Drug Carriers; Apoferritins; liposomy; Animals; lidé; Drug Compounding; Humans; zvířata; Antibiotics, Antineoplastic; koně; příprava léků; inhibiční koncentrace 50; nádorové buněčné linie; nosiče léků; Dose-Response Relationship, Drug; Doxorubicin; Horses